A new “giant” species of Maranta L. (Marantaceae) from the Atlantic Forest of northeastern Brazil - Luna, Naédja; Pessoa, Edlley; Alves, Marccus (Phytotaxa, 2018)
A new species of Maranta subg. Maranta, M. gigantea, is described and illustrated. This is known from the submontane Atlantic Forest in the states of Pernambuco and Alagoas (Brazil). Based on the zingiberoid growth form it is morphologically similar to M. anderssoniana and M. zingiberina, differing mainly in the shape of the leaf blade (lanceolate to oblong or ovate respectively vs. narrow-lanceolate) and number of calli in the callose staminode (one prominent callus vs. two prominent calli). It is further differentiated from M. anderssoniana by being larger plants (up to 1.8 m tall vs. up to 1.0 m tall), with a tomentose leaf sheath (vs. sericeous), larger corolla tube length (9−12 mm long vs. 5−6 mm long), asymmetrically elliptical corolla lobes (vs. asymmetrically oblong) and larger outer staminodes (minor 12−15 × 6.5−8 mm vs. 10−11 × 5.5−6 mm and major 13−16 × 8.5 × 10.5 mm vs. 10−12 × 8−9.2 mm). Due to its narrow distribution, it is classified as critically endangered.